Achievement Motivation Training (AMT): MAN 3 Kebumen Career Guidance Graduation - Reni Suci Wahyuni; Dani Rizana (LPPM POLITEKNIK LP3I, 2024)
This Community Service aims to improve the motivation and knowledge of students after graduating from school. Participants in the Achievement Motivation Training (AMT) activity: Career Guidance Graduation are class XII students of MAN 3 Kebumen, Central Java. The methods used are lectures, discussions and questions and answers with students. The results of this community service activity are that it can help students prepare themselves for the future. By providing information about career choices that can improve work readiness, help plan further education, reduce unemployment, help form career identity, and overcome psychological and social barriers, career guidance can help students achieve success in their careers and live a satisfying life.